A Thematic Synthesis on Empathy in Software Engineering based on the Practitioners' Perspective - Cerqueira, Lidiany; Freire, Sávio; Bastos, João; Spínola, Rodrigo; Mendonça, Manoel; Santos, José (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Context: Empathy is the ability to understand and share the emotions of others. Despite its relevance for research and practice in software engineering, it is still an under-researched topic. Aims: To investigate the meaning, importance, practices, and effects of empathy from the perspective of software practitioners. Method: We apply a thematic synthesis of grey literature. We analyzed 22 articles from DEV, an online community used by software developers. Results: We found that empathy has different meanings for software practitioners. The word is used to express understanding, compassion, and perspective-taking, among other meanings. Practitioners consider empathy important, undervalued, needed, and wanted. The study points out 19 empathetic practices in SE, such as adopting good programming practices, understanding others, being compassionate, and being mindful. It also lists 28 effects of these practices, including quality improvement, better products, and build trust. Conclusion: We organize this body of knowledge in a framework supporting new research efforts. The framework may also support software professionals to develop empathetic skills in SE.